Paediatric Wolfram syndrome Type 1: should gonadal dysfunction be part of the diagnostic criteria? - Frontino, Giulio; Di Tonno, Raffaella; Stancampiano, Marianna Rita; Arrigoni, Francesca; Rigamonti, Andrea; Morotti, Elisa; Canarutto, Daniele; Bonfanti, Riccardo; Russo, Gianni; Barera, Graziano; Piemonti, Lorenzo (Frontiers in Endocrinology, 2023)
Aims Wolfram Syndrome Spectrum Disorder (WFS1-SD), in its “classic” form, is a rare autosomal recessive disease with poor prognosis and wide phenotypic spectrum. Insulin dependent diabetes mellitus (DM), optic atrophy (OA) diabetes insipidus (DI) and sensorineural deafness (D) are the main features of WFS1-SD. Gonadal dysfunction (GD) has been described mainly in adults with variable prevalence and referred to as a minor clinical feature. This is the first case series investigating gonadal function in a small cohort of paediatric patients affected by WFS1-SD. Methods Gonadal function was investigated in eight patients (3 male and 5 female) between 3 and 16 years of age. Seven patients have been diagnosed with classic WFS1-SD and one with non-classic WFS1-SD. Gonadotropin and sex hormone levels were monitored, as well as markers of gonadal reserve (inhibin-B and anti-Mullerian hormone). Pubertal progression was assessed according to Tanner staging. Results Primary hypogonadism was diagnosed in 50% of patients (n=4), more specifically 67% (n=2) of males and 40% of females (n=2). Pubertal delay was observed in one female patient. These data confirm that gonadal dysfunction may be a frequent and underdiagnosed clinical feature in WFS1-SD. Conclusions GD may represent a frequent and earlier than previously described feature in WFS1-SD with repercussions on morbidity and quality of life. Consequently, we suggest that GD should be included amongst clinical diagnostic criteria for WFS1-SD, as has already been proposed for urinary dysfunction. Considering the heterogeneous and elusive presentation of WFS1-SD, this clinical feature may assist in an earlier diagnosis and timely follow-up and care of treatable associated diseases (i.e. insulin and sex hormone replacement) in these young patients.